2016
DOI: 10.1097/scs.0000000000002498
|View full text |Cite
|
Sign up to set email alerts
|

Iliac Crest Donor Site for Children With Cleft Lip and Palate Undergoing Alveolar Bone Grafting

Abstract: The authors aimed to accurately assess the donor site morbidity from iliac crest bone grafts for secondary bone grafting in patients with cleft lip and palate alveolar defects. Fifty patients between 3 months and 10 years following alveolar bone grafting for cleft lip and palate were entered into the study. Two-thirds of patients had no significant concerns about the donor site. The remaining third had some concerns about the appearance of their hips and less than 10% of patients expressing strong agreement wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In 2016, Wheeler et al16 conducted a retrospective study to accurately assess donor site morbidity from iliac crest bone harvesting for secondary bone grafting in patients with cleft lip and palate alveolar defects. Fifty patients (32 males and 28 females) were included.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Wheeler et al16 conducted a retrospective study to accurately assess donor site morbidity from iliac crest bone harvesting for secondary bone grafting in patients with cleft lip and palate alveolar defects. Fifty patients (32 males and 28 females) were included.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier secondary bone grafting around the ages of 4‐7 years may be indicated prior to the eruption of lateral incisors or if the cleft is mesial to the lateral incisor . Secondary bone grafting can be a difficult surgical procedure to undertake with a degree of morbidity, particularly at the donor site . The success of the graft, as measured by bone fill, can be variable with poorer results reported when grafting has been delayed after the canine has erupted or where there is a flap dehiscence complication post‐graft .…”
Section: Introductionmentioning
confidence: 99%
“…30–34 Over time, studies by Swan and Goodacre, Rawashdeh and Telfah, Baquain et al, Kolomvos et al, and Wheeler et al demonstrated that open iliac bone harvest was well-tolerated by patients and had relatively low complication rates. 19,35–38 For the most part, patient experiences of pain from the iliac donor site were within expectations and lasted only a few days, most considered the scar acceptable, and few patients experienced long-term morbidity such as paresthesia or significant contour deformities. 39 Still, surgeons seeking to further reduce donor-site morbidity studied various methods of minimally invasive iliac bone harvest using methods such as French’s osteotome, Shepard’s osteotome, power-driven trephine, trocar and trephine, cylinder bone extractor, and trephine burrs.…”
Section: Discussionmentioning
confidence: 99%